Paleosols as An Alternative Method to Define Sequence Boundary in Fluvial System: A Case Study in Semberah Field, Kutei Basin - Edy Kurniawan (Ikatan Ahli Geologi Indonesia, 2011)
Difficulties in reconstructing sequence stratigraphic framework of the Semberah Area, East Kalimantan, have brought up an idea to use paleosols to solve the problems. The Semberah Area has dominantly fluvial deposits, which are characterised by the presence of many erosional channel bases. In a vertical sequence, the erosional channel base cannot be easily distinguished from a sequence boundary, therefore, in order to help in sequence stratigraphic interpretation, a research on paleosols of the Semberah Field, Kutai Basin, has been undertaken.The research mostly utilizes outcrop data above the Semberah Field, where the equivalent of the producing units is exposed. The outcrops are correlated to subsurface well data (logs and cores) and seismic lines to analyze their significance in the Sequence Stratigraphic Framework. A total of 21 outcrops have been described sedimentologically and subsequently investigated for their paleosol occurrences. The research documents 52 discreet occurrences of paleosols in the Semberah outcrops with individual paleosol thickness ranges from 25 to 225 cm. The results of the research show that paleosols are found ubiquitously in deltaic sediments in the Semberah Field. The common distributions of paleosols in the Semberah area consist of Argilisol 16%, Histosol 16%, Oxisol 8%, Protosol 6%, Spodosol 50% and Vertisol 4%. The Gleysol, Calcisol and Gypsisol are not found. The occurrence of paleosols within a Highstand Systems Tract (HST) is 70.6% well-developed with maturity varies from weak to moderate (stage 2 to 4). The low accommodation space supports paleosols to develop well with its upper boundary most likely is associated with sequence boundary. The paleosol distribution within an Incised Valley Fill (IVF), Lowstand System Tract (LST) and Transgressive Surface of Erosion (TSE) are very well developed with percentage of their occurrence as 3.9%, 1.9% and 1.96% with their maturity varies from moderate to strong (stage 4 to stage 5). In general, they will associate with an erosional channel base known as sequence boundary at the bottom end border. Paleosols are not found in the beginning of Transgressive System Tract (TST) in Semberah area which is commonly characterized by the occurrence of Hydromorphic Paleosol. During the Transgressive System Tract (TST), the paleosols are not well developed or even obstructed with percentage of their occurrence within the area as 21.5% and the maturity varies from stage 2 to stage 3.